Criminal Acts of Corruption by State Officials in Procurement of Goods and Services: Study of the Role of Justice Collaborators and Whistleblowers in the Age of Technology - Alfitra, Alfitra; Rambe, Mara Sutan; Yanto, Oksidelfa; Bahtiar, Ahmad (Journal of Indonesian Legal Studies, 2025)
This study aims to determine and analyze the role of justice collaborators and whistleblowers in corruption in the procurement of goods and services carried out by state administrators and to determine the forms of corruption that occur in the procurement of goods/services. The research method used is normative legal research through a legislative approach and a conceptual approach. The results of this study found several problems, namely; There is a need for unification of perceptions and synchronization of regulations that apply to law enforcement officers in understanding aspects of witness protection related to legal collaborators and violation reporters. The most common forms of deviation in the government procurement of goods/services that can lead to corruption are: bribery, job combination, separation of duties, collusion between partners providing goods/services and procurement implementers, document falsification, waste of money. region/country, reducing the quantity and/or quality of coral/gauze, incorrectly determining the type of procurement contract for goods/services, contracts without available budget, setting their own estimated price that is too high.